RHINOCEROS APPLICATION LEARNING TRAINING FOR ARCHITECTURE ALUMNI - Aiyub, Hendra; Safyan, Adi; Hutasuhut, Alvin Azhar; Yamesa, Andrit (Universitas Muhammadiyah Aceh, 2022)
In the globalization era, increasingly fierce industrial competition demands the optimization of allavailable resource to produce high quality products, so the companies can compete with others, aswell as for human resources. Nowadays, most of the jobs are done digitally, but not all workers inthe industry have digital skills. The same condition happens in the Indonesian Architecture,Engineering, and Construction (AEC) sector. Even though it has made a major contribution to thedevelopment of Indonesian industry, the digital skills of its human resources are still weak. Thecompetition in the world of architecture is getting harder. It is inevitable that free competition willlead architects into laws of nature, which means that architecture graduates with better abilities cansurvive dan able to adapt to the demands of space, time and technology. Likewise, skills in 3-dimentional modelling in the world of construction. This ability is quite important in the worldconstruction or the world of architectural consulting, as a way to visualize designs in an attractiveway. One of the applications that provides 3D modelling features is Rhinoceros. The results obtainedin this community service are a media publication, collaboration between Malikussaleh Universityand architecture alumni in Lhokseumawe city, and publication in a scientific journal. This service alsohas a positive impact on the alumni to have digital 3D modelling skills using Rhinoceros software.Keywords: Modelling, Rhinoceros, Consultants, Architecture